Porphyry and Daniel 7: academic discussions between Maurice Casey and Arthur Ferch - Maluf, Lilian Chaves (Revista Archai, 2010)
The first Jewish interpretations, as well as the first Christian commentaries, on the Book of Daniel, are unanimous about an idea: that of the authority of the prophet Daniel. Porphyry from Tyre, being the first one to point out to the macabaic composition of the book and challenging the prestige of the figure of the prophet, questioned the foundations for which Christianity was justifying the legitimacy of its religious practices. By which ways has Porphyry prepared his arguments is the question that separates Casey and Ferch in different ways.